Improved security and stability of grid connected the wind energy conversion system by unified power flow controller - I Made Wartana; Ni Putu Agustini; Sasidharan Sreedharan (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The stability and security improvements of the grid-connected to the wind energy conversion system (WECS) can be made by optimizing the placement of a flexible alternating current transmission system (FACTS). This study discusses the optimal placement of one type of WECS, namely the doubly-fed induction generator (DFIG) with a series and a shunt-FACTS control device called unified power flow controller (UPFC). The DFIG and UPFC connected grid dynamic perfor mance improvement with a maximum load bus system scenario. The optimal placement of DFIG and UPFC on the grid is formulated as a multi - objective problem, namely maximizing load bus system (Max. LBS) while minimizing active power loss (Min. P loss ) by pleasi ng numerous security and stability constraints. The non-dominated sorting genetic algorithm II (NSGA-II) have been utilized to settle this opposed bi-objective enhancement problem. The validity of the suggested method was examined on a modified IEEE 14-bus and a utilitarian examine system connected to DFIG with UPFC in power system analysis toolbox ( PSAT ) software. The optimal placement of DFIG and UPFC on the grid has increased the system's dynamic performance, with all the specified particular constraints being encountered.